Microwave-assisted synthesis of ZnO–Y3Al5O12:Ce3+ composites with enhanced visible light photocatalysis - Liu, Xinjuan (2013)
ZnO–Y3Al5O12:Ce3+ composites were successfully synthesized via a microwave-assisted reaction of the ZnO precursor with a Y3Al5O12:Ce3+ suspension using a microwave synthesis system. The morphology, structure and photocatalytic performance in the degradation of methylene blue (MB) were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction spectroscopy, fluorescence spectrophotometer, and UV-vis absorption spectrophotometer. The results show that the introduction of Y3Al5O12:Ce3+ can enhance the photocatalytic performance of ZnO with a maximum MB degradation rate of 93% under visible light irradiation compared with pure ZnO (13%) mainly due to the light down-converting effect of Y3Al5O12:Ce3+, which facilitates the self-sensitized destruction of MB.